Eggshell Powder as an Adsorbent for Removal of Fluoride from Aqueous Solution: Equilibrium, Kinetic and Thermodynamic Studies - R. Bhaumik; N. K. Mondal; B. Das; P. Roy; K. C. Pal; C. Das; A. Baneerjee; Jayanta kumar Datta (E-Journal of Chemistry)
A new medium, eggshell powder has been developed for fluoride removal from aqueous solution. Fluoride adsorption was studied in a batch system where adsorption was found to be pH dependent with maximum removal efficiency at 6.0. The experimental data was more satisfactorily fitted with Langmuir isotherm model. The kinetics and the factor controlling adsorption process fully accepted by pseudo-second-order model were also discussed. Ea was found to be 45.98 kJmol-1 by using Arrhenius equation, indicating chemisorption nature of fluoride onto eggshell powder. Thermodynamic study showed spontaneous nature and feasibility of the adsorption process with negative enthalpy (∆H0) value also supported the exothermic nature. Batch experiments were performed to study the applicability of the adsorbent by using fluoride contaminated water collected from affected areas. These results indicate that eggshell powder can be used as an effective, low-cost adsorbent to remove fluoride from aqueous solution as well as groundwater.